2022
DOI: 10.1038/s41420-022-00899-5
|View full text |Cite
|
Sign up to set email alerts
|

FAS receptor regulates NOTCH activity through ERK-JAG1 axis activation and controls oral cancer stemness ability and pulmonary metastasis

Abstract: Pulmonary metastasis occurring via the colonization of circulating cancer stem cells is a major cause of oral squamous cell carcinoma (OSCC)-related death. Thus, understanding the mechanism of OSCC pulmonary metastasis may provide a new opportunity for OSCC treatment. FAS, a well-known apoptosis-inducing death receptor, has multiple nonapoptotic, protumorigenic functions. Previously, we found that SAS OSCC cells with FAS receptor knockout did not affect orthotopic tumor growth or cervical lymph node metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Stimulation of T cells by EGFR may affect the activity of the NOTCH pathway in PVL cells. 63 At the same time, FASLG on the surface of T cells and the FAS of PVL cells interacted, and the FAS receptor regulated NOTCH pathway signaling by activating the ERK-JAG1 axis, 64 which provides further evidence of the effect of T cells on PVL cells ( Figure 6 K). The NOTCH pathway promotes angiogenesis and breast cancer metastasis.…”
Section: Resultsmentioning
confidence: 82%
“…Stimulation of T cells by EGFR may affect the activity of the NOTCH pathway in PVL cells. 63 At the same time, FASLG on the surface of T cells and the FAS of PVL cells interacted, and the FAS receptor regulated NOTCH pathway signaling by activating the ERK-JAG1 axis, 64 which provides further evidence of the effect of T cells on PVL cells ( Figure 6 K). The NOTCH pathway promotes angiogenesis and breast cancer metastasis.…”
Section: Resultsmentioning
confidence: 82%
“…The JAG1-Notch pathway facilitates tumor metastasis via various carcinogenic mechanisms [22][23][24] . Cohen et al 25 found that cyclin D1 is a downstream transcription target of the JAG1-Notch pathway, and knockdown of the JAG1 gene decreases cyclin D1 level, arresting the cell cycle in the G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…The JAG1-Notch pathway facilitates tumor metastasis via various carcinogenic mechanisms [22][23][24] . Cohen et al found that cyclin D1 is a downstream transcription target of the JAG1-Notch pathway, and knockdown of the JAG1 gene decreases cyclin D1 level, arresting cell cycle in G1 phase 25 .…”
Section: Discussionmentioning
confidence: 99%